Klasifikasi Ilmu Pengetahuan Barat dan Islam serta Konstribusinya dalam Dunia Akademik - Ramandha Rudwi Hantoro (TASAMUH: Jurnal Studi Islam, 2022)
Abstract The dichotomy of science and Islamic science has been a long and influential discussion in the development of Islamic scholarship itself. This article describes the classification of Western and Islamic science in terms of the history of the development of the philosophy of science, where science has the same root or source and is not dichotomous. The method used in this article is the “literature review” method. The data used as research sources come from research results, scientific journals, manuscripts / turats, and relevant books related to the classification of science. The results of the study show that the classification of science began to develop since the existence of philosophers from Greece, such as: Plato, Socrates, and others as well as Islamic thinkers such as: al-Kindi, Ibn Sina, Ibn Kholdun and others who were concerned in science. Since the 3rd century Hijri / 9 AD, the discussion of science has begun to develop, even the classification of science into several scientific categories such as natural science, mathematics, and linguistics has become the subject of study by Islamic philosophers and thinkers for pedagogical didactic interests. At a later stage that the philosophy of science has an important role in the development of science, even the philosophy of science underlies the thought of the birth of the scientific method in academia, such as: qualitative and quantitative research methodologies.